Market Segmentation, Cannibalization, and the Timing of Product Introductions - Moorthy, K. Sridhar; Png, I. P. L. (Management Science, 1992)
Consider a seller who faces two customer segments with differing valuations of quality of a durable product. Demand is stationary and known, the technology exists to release two products simultaneously, and the seller can commit in advance to subsequent prices and qualities. Should he introduce two differentiated products at once or one at a time? Under the simultaneous strategy, the lower quality would cannibalize demand for the higher quality. To reduce cannibalization, the seller could lower the quality of the low-end model and reduce the price of the high-end. Alternatively, he could increase the quality of the low-end model, but delay its release. Sequential introduction, however, would mean that the profits from the low-end model arrive later. We show that sequential introduction is better than simultaneous introduction when cannibalization is a problem and customers are relatively more impatient than the seller. However, when the seller cannot pre-commit, sequential selling is much less attractive because then he cannot use his product designs to alleviate cannibalization.